Methods to improve teaching effciency for students from the People’s Republic of China at technical universities - K. P. Baslyk; V. P. Pechnikov; N. A. Tukhtarova (Открытое образование (Москва), 2019)
The purpose of the study is to develop guidelines for improving the teaching process of students from the People’s Republic of China in Russian technical universities, taking into account the specific aspects of higher education in China and methodology of teaching special disciplines to foreign students in Russia. The urgency of the research is caused by the global trends in the development of higher education: globalization, liberalization and internationalization, the growth of cooperation between the two countries in the field of science and technology, in particular space exploration, which as a result leads to the development of joint programs in the provision of education services. Most scientific articles on teaching foreign students are devoted to general issues of pedagogy and psychology, as well as to the problems of teaching Russian as a foreign language, while the aspects of teaching special technical disciplines to citizens of another country pose certain challenges.Materials and methods of research. The research materials include printed works for which the appropriate methods of analysis of scientific texts are used: ● excerpts from the development programs of space industry and joint educational programs of Russia and China – aspect and diachronic method of analysis of priority areas of development of the higher school of China and promising areas of cooperation; ● the curricula of professional education in various areas and specialties of Bauman Moscow State Technical University – aspect analysis of the general provisions of engineering training programs; ● manuals on the “Basics of Rocket and Space Technology” (BRST) of Russia (USSR) and China – critical, comparative and conceptual analysis of the content features, methods and style of presentation of the material; ● BRST – aspect and phenomenological analysis of the structure and content of a special technical discipline; ● scientific works on pedagogy and psychology – aspect and system analysis of features of the education system, educational behavior and bilingual opportunities of students from China.The paper applied the problem analysis method to tackle the task in the context of publications’ shortage on teaching special technical disciplines to foreigners. Also, the method of deconstruction, axiomatic and descriptive analysis of text textbooks and manuals on pedagogy and psychology is directly utilized to develop guidelines, proposed in the article.Results. Upon the analysis, guidelines to improve the efficiency of the educational process for Chinese students were developed, using teaching based on the printed text in Russian and Chinese, transformation of educational material to another type, and inclusion of nationally oriented content in educational materials. Finally, we proposed original methods of express surveys to establish feedback with students and put forward a conceptual suggestion, that foreign students pursuing technical education should be given the opportunity and conditions for the implementation and development of cognitive abilities using their native language.Conclusion. The developed pedagogical methods allow to adapt the educational material of special technical disciplines taking into account both mental and socio-cultural characteristics of the students from the People’s Republic of China studying in the universities of the Russian Federation.